Penurunan NG Flow Out & NG Ratio Menggunakan Metode Lean Six Sigma - DMAIC - Setyawan, Sony; Supriyati (DPPM Universitas Pelita Bangsa, 2024)
PT. XYZ is a manufacturing company engaged in the automotive component sector that produces Sub Assembly products for two-wheeled and four-wheeled vehicles. In a great line, the steps of Bracket Comp Pivot production process consist of five processes, such as : process Blank Pierce and Stamping in the Small Press Line, the Spot and Sub-Assy stages in the Assy Welding Line, and the checking stage in the Final Inspection Line. This final research paper was conducted in Assy Welding Line where the line produced part of Bracket Comp Pivot and Line Final Inspection. Based on the data of NG Outflow & NG Ratio on the periods of January until July 2022, it was obtained about 57 pcs of defect Spot types and the total of defect Internal process was about 32.325 PPM which was equivalent with sigma level 3,3. After it was applied through six sigma method, the total of NG Outflow was nil (0 pcs) and the level of product defect can be relegated to 7.500 PPM which was equivalent with sigma level 4.